Simulation of nitrogen release from chitosan/local organic fertilizer composite as slow-release fertilizer - Alit Istiani; Yuni Kusumastuti; Rochmadi (Jurnal Rekayasa Proses, 2020)
The application of conventional fertilizer, especially for inorganic fertilizer, has low efficiency due to the fast release of its nutrients into the environment. Also, it has a high operating cost caused by multiple fertilization processes in one of the planting periods. One of the possibilities to overcome this limitation is applying organic fertilizer as a slow-release fertilizer (SRF). The objective of this research is to prepare SRF by modifying the formulation of local organic fertilizer with chitosan as a binder. The rate of the nitrogen release was studied and simulated with MATLAB. The result shows that the nitrogen loss by water leaching decreased up to 85% in chitosan/organic fertilizer rather than the fertilizer without chitosan. By MATLAB simulation, the release of nitrogen has followed the proposed mathematical model in which the mass transfer occurred dominated by diffusion mechanism with the diffusivity coefficient of 1.61x10-5 cm2/s.